Sex, power and consent youth culture and the unwritten rules - Powell, Anastasia (Cambridge University Press, 2010)
Sex, Power and Consent: Youth Culture and the Unwritten Rules draws on the real world stories and experiences of young women and young men - as told in their own words - regarding love, sex, relationships and negotiating consent. Judicious reference to feminist and sociological theory underpins explicit connections between young people's lived experience and current international debates. Issues surrounding youth sex within popular culture, sexuality education and sexual violence prevention are thoroughly explored. In a clear, incisive and eminently readable manner, Anastasia Powell develops a compelling framework for understanding the 'unwritten rules' and the gendered power relations in which sexual negotiations take place. Ultimately Sex, Power and Consent provides practical strategies for young people, and those working with them, toward the prevention of sexual violence